2014
DOI: 10.1002/lsm.22255
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of hexaminolevulinate photodynamic therapy in patients with low‐grade cervical intraepithelial neoplasia

Abstract: HAL PDT shows a favorable efficacy and safety profile and represents a promising alternative to observation and surgical procedures in patients with CIN 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…1). Moreover, the risks of bias for randomization and allocation in three RCTS [2426] are unclear. The 2015 study by Hillemanns et al [25] represents the largest study with a weight of 48.1% in the meta-analysis of CRR in CIN patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Moreover, the risks of bias for randomization and allocation in three RCTS [2426] are unclear. The 2015 study by Hillemanns et al [25] represents the largest study with a weight of 48.1% in the meta-analysis of CRR in CIN patients.…”
Section: Resultsmentioning
confidence: 99%
“…Fu et al [26] represents the largest study with a weight of 48.6% in the meta-analysis of CRR in cervical HPV. The 2014 study by Hillemanns et al [24] is the largest study with a weight of 86.8% in the meta-analysis of AER in patients receiving PDT. Moreover, the total number of events with each outcome was less than 300.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high rate of spontaneous HPV clearance, no significant difference was seen in the eradication of high risk HPV between the PDT and the control groups. Nevertheless, HAL-PDT showed high clearance rates and a favourable safety profile compared to surgery [ 245 ]. A follow-up study showed no significant effect of HAL-PDT compared to placebo groups for CIN1/2, but a significantly improved response was seen compared to placebo in CIN2 patients, which sustained towards the 6-month follow up.…”
Section: Pdt In Clinical Trialsmentioning
confidence: 99%
“…In gastroenterology, PDT demonstrated its effectiveness for the treatment of superficial cancers of the esophagus in patients ineligible for further treatment, with a postradiation recurrence, severe dysplasia in Barrett, and unresectable cholangiocarcinoma [59]. In gynecology, the interest of PDT has been shown in the treatment of cervical dysplasia of low-and high-grade cervical lesions [60]. Our team developed folic acid-targeted photosensitizers that could be very efficient to treat peritoneal carcinosis, and a preclinical evaluation is under progress [61,62].…”
Section: Generalitiesmentioning
confidence: 99%